The biological prospective of red-pigmented bacteria cultured from contaminated agar media - Achmad Arifiyanto; HAPIN AFRIANI; MEISHY HANDERLIN PUTRI; BERLIANA DAMAYANTI; CINDY LUKYTA RATIH RIYANTO (Society for Indonesian Biodiversity, 2021)
Abstract. Arifiyanto A, Afriani H, Putri MH, Damayanti B, Riyanto CL. 2021. The biological prospective of red-pigmented bacteria cultured from contaminated agar media. Biodiversitas 22: 1152-1159. Contaminated agar media was often depleted due to the growth of microbes, which is undesirable for culture. However, the contaminating microbes usually have a distinctive morphology. This research aimed to identify the potential of red-pigmented bacteria originated from the contamination of Drosophila melanogaster larvae. Fruit fly larvae that grow on contaminated tryptic soy agar were accompanied by the appearance of the red-pigmented bacteria colony. The bacterial colonies were purified by the re-streaking method on tryptic soybean agar. This strain was characterized morphologically, biochemically, and molecularly. Results showed that the MBC1 strain was identified as Serratia marcescens. The various metal susceptibility tests at 25 ppm did not affect the growth of the MBC1 strain. Meanwhile, it was also able to inhibit the growth of certain pathogens such as Aspergillus niger, Candida sp., Fusarium sp., and Rigidoporous sp. Strain MBC1 was able to produce antioxidant compounds. The lipolytic and amylolytic activity can be developed for bioremediate agriculture waste and biosurfactant production.